The Role of Microteaching in Preparing Prospective Teachers to Face Field Experience Practices - Ramdan Nafilah; M. Azhar Busaeri Putra; Fredy Ismail; Euis Latipah (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Microteaching is one of the effective assessment methods in preparing prospective teachers before implementing field experience practice (PPL). This technique provides an opportunity for education students to master basic teaching skills in a controlled environment, with a short duration and focus on specific aspects such as classroom management, use of learning media, and evaluation techniques. Through microteaching, prospective teachers can identify their strengths and weaknesses, as well as obtain constructive feedback from lecturers and peers. Research shows that the microteaching experience significantly increases the confidence, creativity and pedagogical competence of prospective teachers, making it easier for them to adapt to real situations in schools during PPL. Thus, microteaching acts as a bridge between educational theory in higher education and teaching practice in the field, making it a critical component in the teacher education curriculum.